Refleksi Filosofis Atas Perkembangan Ilmu-ilmu Humaniora - Rizal Munstansyir (Jurnal Filsafat "WISDOM", 2003)
In the 19th scientific world was almost dominated by natural science. This condition influenced the separation between natural and non-natural sciences. The questions which were derivated from the separation: 1. are any differences in quality between the two separation of science? 2. how did the humanities function to intergrate of scientific activity? To answer those questions this paper attempt to invertigate the brief development of them, especially in Indonesia